Targeting of autoantigens to DEC205+ dendritic cells in vivo suppresses experimental allergic encephalomyelitis in mice - Ring, Sabine; Maas, Michael; Nettelbeck, Dirk M.; Enk, Alexander; Mahnke, Karsten (The journal of immunology, 2013)
The dendritic and epithelial cell receptor with a m.w. of 205 kDa (DEC205) is expressed by dendritic cells (DCs) and facilitates Ag presentation. After injection of Ags coupled to Abs specific for DEC205 into mice, Ag presentation occurs by nonactivated DCs, which leads to induction of regulatory T cells (Tregs). To test this system for tolerance induction in experimental allergic encephalomyelitis (EAE), we created single-chain fragment variables (scFv) specific for DEC205 and fused the scFv to the self-Ag myelin oligodendrocyte glycoprotein (MOG; scFv DEC:MOG). An anti-β-galactosidase scFv:MOG fusion protein (scFv GL117:MOG) served as isotype control. After staining of DCs in vitro with purified scFv DEC:MOG, binding to DCs and colocalization with MHC class II was apparent, whereas isotype controls did not bind. We next injected scFv DEC:MOG into mice and observed elevated numbers of highly activated, IL-10-producing CD4+CD25+Foxp3+ Tregs (17% of CD4) in spleens, as compared with isotype controls and uninjected mice (12% of CD4). Furthermore, DCs isolated from scFv DEC:MOG-injected animals produced significantly increased levels of TGF-β. Most importantly, when EAE was induced in scFv DEC:MOG-injected mice, 90% of the mice were protected from EAE, whereas all mice in the isotype controls (scFv GL117:MOG) experienced development of EAE. When applying scFv DEC:MOG to mice that had already experienced EAE symptoms, abrogation of the disease in 90% of the animals was apparent, whereas all animals in the control groups experienced development of severe EAE. Thus, these data indicate that targeting of MOG to “steady-state” DCs in vivo may provide a tool to prevent and to treat EAE by a DC/Treg-driven mechanism.
Im Text ist "+" hochgestellt
Gesehen am 13.01.2022